INFLUENCE OF AUXINS ON RIZOGENESIS OF ACTINIDIA KOLOMIKTA CULTIVARS IN CULTURE IN VITRO - Borodulina, I. D.; Plaksina, T. V. (Acta Biologica Sibirica, 2016)
The influence of growth regulators of axin nature on rooting of actinidia kolomikta in culture in vitro has been studied. This species of actinidia is the most-hardy that in conditions of Western Siberia is actual and resistant to pests as well. It differs by early ripening, bears from the three-year age. This species lives over 50 years. The objects of the study were two female forms of actinidia cultivars – Moma and Prevoskhodnaya. The fruits of these cultivars are cylindrical, green and dark-green, with longitudinal strips. The taste of berries of the cultivar Moma is very sweet, with pineapple aroma, as for Prevoskhodnaya – sour sweet. Fruits of the cultivar Moma are not deciduous, don’t fell off at ripening. Micro cuttings with two buds were as explants. 12 variants of nutritional media on the base of medium Murashige Skoog, supplemented with growth regulators of auxin nature (IBA, IAA, NAA), were tested. It’s established, that at the stage of rooting it’s advisable to use relatively low concentrations of auxins: 0.5–1.0 µM NAA and 1.0 µM IBA. Effective concentrations and type of auxin are defined for each cultivar.